2017
DOI: 10.1007/s00213-017-4703-9
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone and aripiprazole alleviate prenatal valproic acid-induced abnormalities in behaviors and dendritic spine density in mice

Abstract: These findings indicate that chronic risperidone and aripiprazole treatments improve VPA-induced abnormalities in behaviors and prefrontal dendritic spine density, which may be mediated by repeated elevation of extracellular DA in the prefrontal cortex. Our results also imply that loss of prefrontal dendritic spines may be involved in the abnormal behaviors in the VPA mouse model of ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 52 publications
4
19
1
Order By: Relevance
“…Notably, Hara et al ( 2016 ) found that inhibition of DAT by atomoxetine and methylphenidate has beneficial effects on VPA-induced ASD phenotypes, but not on NET (Hara et al, 2016 ). These findings are consistent with there being increased extracellular dopamine levels in the prefrontal cortex of VPA-induced ASD animal models after chronic risperidone treatments (Hara et al, 2017 ).…”
Section: Dysregulation Of Monoamine Transmission In Asdsupporting
confidence: 84%
See 1 more Smart Citation
“…Notably, Hara et al ( 2016 ) found that inhibition of DAT by atomoxetine and methylphenidate has beneficial effects on VPA-induced ASD phenotypes, but not on NET (Hara et al, 2016 ). These findings are consistent with there being increased extracellular dopamine levels in the prefrontal cortex of VPA-induced ASD animal models after chronic risperidone treatments (Hara et al, 2017 ).…”
Section: Dysregulation Of Monoamine Transmission In Asdsupporting
confidence: 84%
“…Chronic treatments with 8-OH-DPAT, a 5-HT 1A receptor agonist, not only ameliorates fear memory extinction and social impairment, but also normalizes the E/I balance within the amygdala (Wang et al, 2013 ). Hara et al ( 2017 ) found that aripiprazole (an atypical antipsychotics that acts as a 5-HT 1A receptor agonist and a partial agonist of D2R in order to reduce DA transmission) and risperidone (an atypical antipsychotics that inhibits D2R and the 5-HT 2A receptor), but not haloperidol, are able to alleviate reverse recognition memory deficits and social impairment of VPA-treated rats, as well as restoring the reduced number of dendritic spines in the mPFC of VPA-treated rats (Hara et al, 2017 ). Abnormal vocal communication and striatal compartmentation in VPA-treated mouse neonates are also partially rescued by chronic risperidone treatment after birth (Kuo and Liu, 2017 ).…”
Section: Dysregulation Of Monoamine Transmission In Asdmentioning
confidence: 99%
“…Importantly, pre-registering studies would further separate pre-diction and post-diction analyses to better delineate the relationship between hypothesis and results, and to better compare different results [73,74]. As noticed in the therapeutic studies (Table 4), a publication bias appears to exist, whereby only successful treatments have generally been published, whereas unsuccessful treatment trials have not been reported (with the exception of haloperidol [75]).…”
Section: Effectiveness Of Novel Pharmacotherapies In the Vpa Model Anmentioning
confidence: 99%
“…HRW (H 2 concentration >1.8 mg/L, 245 mL) generously provided by Beijing Hydrovita Beverage Co. Limited (Beijing, China) and stowed at ambient pressure and temperature in an aluminum can with no head space. VPA (purchased from Sigma-Aldrich, Shanghai, China) was used following the procedure of previous reports to induce autistic-like behavior in mice (Al-Amin et al, 2015 ; Hara et al, 2017 ; Yamaguchi et al, 2017 ). VPA was dissolved in 0.9% NaCl solution, and the volume of injection was 10 mL/kg.…”
Section: Methodsmentioning
confidence: 99%